Generation of an induced pluripotent stem cell line (DHMCi008-A) from an individual with TUBA1A tubulinopathy - Schröter, Julian; Syring, Hanna; Göhring, Gudrun; Kölker, Stefan; Opladen, Thomas; Hoffmann, Georg F.; Syrbe, Steffen; Jung-Klawitter, Sabine (Stem cell research, 2022)
Variants in different neuronal tubulin isotypes cause severe neurodevelopmental disorders with cerebral malformations accompanied by developmental delay, motor impairment, and epilepsy, known as tubulinopathies. Induced pluripotent stem cells were generated from peripheral blood mononuclear cells from a female subject carrying the heterozygous de novo variant c.[521C > T] (p.[Ala174Val]) in the TUBA1A gene. PBMCs were reprogrammed using the CytoTune™-iPS 2.0 Sendai Reprogramming Kit (Invitrogen) and showed a normal karyotype, expression of pluripotency markers, and spontaneous in vitro differentiation into all three germ layers. The generated iPSCs represent a useful tool to study the pathophysiology of TUBA1A tubulinopathy.
Gesehen am 06.07.2022